Human papillomavirus 16 promotes microhomology-mediated end-joining - Leeman, Jonathan E. (Proc Natl Acad Sci U S A, 2019)
Squamous cell carcinomas (SCCs) arising from aerodigestive or anogenital epithelium that are associated with the human papillomavirus (HPV) are far more readily cured with radiation therapy than HPV-negative SCCs. The mechanism behind this increased radiosensitivity has been proposed to be secondary to defects in DNA repair, although the specific repair pathways that are disrupted have not been elucidated. To gain insight into this important biomarker of radiosensitivity, we first examined genomic patterns reflective of defects in DNA double-strand break repair, comparing HPV-associated and HPV-negative head and neck cancers (HNSCC). Compared to HPV-negative HNSCC genomes, HPV+ cases demonstrated a marked increase in the proportion of deletions with flanking microhomology, a signature associated with a backup, error-prone double-strand break repair pathway known as microhomology-mediated end-joining (MMEJ). Then, using 3 different methodologies to comprehensively profile double-strand break repair pathways in isogenic paired cell lines, we demonstrate that the HPV16 E7 oncoprotein suppresses canonical nonhomologous end-joining (NHEJ) and promotes error-prone MMEJ, providing a mechanistic rationale for the clinical radiosensitivity of these cancers.